The City and Nature - Tovmasyan, Eduard (project baikal, 2016)
Animate “nature–1” around us is transforming into supported or non-supported by man “nature-2” within the framework of the urban development of town areas. Interaction of town and nature is a bilateral process. Experts underline 4 groups of town planning risks related to the interaction of town and nature: ecological, natural and biosphere, sanitary-epidemiologic risks as well as planning and management risks. The latter is often connected with protest population activities. The magazine is looking forward to readers comments.